PENGARUH MOTIVASI KERJA, KEPUASAN KERJA DAN KOMITMEN TERHADAP DISIPLIN KERJA PEGAWAI PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET (DPPKA) KABUPATEN TANAH DATAR - Fitria Fitria; Syamsul Amar (Jurnal Riset Manajemen Bisnis dan Publik, 2015)
This research aims to : 1) the effect of work motivation on employee satisfaction, 2) the effect of work motivation on employee commitment, 3) the effect of job satisfaction on employee commitment, 4) the effect of work motivation on employee discipline, 5) the effect of job satisfaction on employee discipline, 6) the effect of commitment to the discipline of employees working at the Department of Finance and Asset Management Revenue (DPPKA) Tanah Datar. The population was Servants Revenue Service Finance and Asset Management (DPPKA) Tanah Datar as many as 72 people. Proportional sampling technique the sample is cluster sampling. Samples numbered 42 people. The data analysis technique used is Path Analysis (Path Analysis). Results of the research are: 1) There is a positive and significant impact work motivation on employee satisfaction, 2) There is a positive and significant impact work motivation on employee commitment, 3) There is a positive and significant effect of job satisfaction on employee commitment, 4) There is a positive influence and significant work motivation on employee discipline, 5) There is a positive and significant impact on the job satisfaction of employee discipline, 6) There is a positive and significant impact employee commitment to the discipline of the Department of Finance and Asset Management Revenue (DPPKA) Tanah Datar. Keywords: Work Motivation, Job Satisfaction, Commitment, Disciplin Work